Pauses of Silence in the Process of Psychotherapy: A Systematic Literature Review - Biteniekytė, Marija; Vaštakė, Marija (Psichologija, 2024)
A pause of silence in the process of psychological counseling and psychotherapy is defined as a moment when neither the therapist nor the client speaks. In the scientific literature, there are not many studies on the phenomenon of pauses of silence. The aim of this article is to describe the meaning and functions of pauses of silence in the psychotherapy process based on the systematic analysis of the literature, which was performed based on PRISMA guidelines. The systematic literature review included 5 scientific articles published in 2019–2024, which are based on qualitative and quantitative research on pauses of silence in the psychotherapy process. A systematic review of the literature found: silent pauses in the process of psychotherapy are an intersubjective phenomenon that depends on both the psychotherapist and the client, as well as on their interaction; the significance of silent pauses depends on the attachment style of psychotherapy clients; the quality and functions of silent pauses vary little depending on the duration of the silent pause; the involvement of the therapist, being in the present moment during the silence pauses, promotes the emergence of insights, introspection of the psychotherapy client, strengthens the therapeutic working alliance, encourages reflection and sharing of one’s feelings, increases the sincerity and raises a general feeling of satisfaction with the psychotherapy process.
Keywords: pauses of silence; psychological counseling and psychotherapy process; psychological counseling; psychotherapy